Acoustic Imaging of In-Duct Aeroengine Noise Sources Using Rotating Beamforming and Phased Arrays - Caldas, Luciano C.; Greco, Paulo C.; Pagani, Carlos C. [UNESP]; Baccala, Luiz A. (Ieee-inst Electrical Electronics Engineers Inc, 2017)
An in-duct rotating beamforming technique, using a wall-mounted array of microphones placed within a long duct, was developed for locating broadband noise sources from an aeroengine fan. The technique was experimentally implemented at the recently constructed long-duct low-speed fan rig test facility at the University of Sao Paulo in Brazil. The test rig has a 16-bladed fan rotor and 14-vaned stator, with speed up to 4250 r/min and a maximum 0.1 Mach number mean axial flow speed. Here, we describe the beamforming details with an emphasis on the mandatory coordinate change to a rotating reference frame for a frequency domain virtual rotating microphone technique. Example sound source maps are presented revealing clear noise blade signatures together with simulated point spread function maps using modal steering vectors at six different frequencies that characterize the beamformer.
Keywords: Aeroacoustic; array signal processing; fan noise; in-duct beamforming; power spectral density; rotating acoustic imaging